Penerapan JIM (Jurisprudential Inqury Model) Pada Pembelajaran Keterampilan Menulis Teks Eksposisi Di Kelas X SMAN MT Bojonegoro - Muhammad Sholehhudin (Jurnal Pendidikan Edutama, 2015)
The aims of this study is to describe the application of JIM (jurisprudential inquiry model) in exposition text writing learning process and, to describe the result of the application. JIM (jurisprudential inquiry mode) learning divides into certain steps, which are focused on: (1) orientate, (2) synthesize, (3) articulate, (4) explore,( 5) refine and (6) evaluate). JIM has spesific purpose to evaluate, critize, or pointing different views to govenrnmental policy, which are connected to the exposition text. The result of the study showed that JIM was accepted by students attentionally, students involved in all process through several steps of learning process. For teacher, JIM possibly teacher to design, asses, and conduct well-planed learning process. The result of the learning process are (1) the ability to create main frame of exposition text is 80,3, (2) the exposition text writing skill average score is 79,2. By analizyng and observing, can be conclused that JIM possibly the students to write in wellplanedd steps, teacher conducted learning intensively and students had high interest of writing.Key words: writing skill, exposition text, jurisprudential inquiry modelÂ